Potensi Pakan Hijauan di Bawah Naungan Pohon Karet Praproduksi dan Produksi di Perkebunan Masyarakat Desa Rukti Sedyo Kecamatan Raman Utara Lampung Timur - Purwa Pramana; Yusuf Widodo; Liman . (JURNAL ILMIAH PETERNAKAN TERPADU, 2012)
The aim of research was know to botany composition, pasture production, and carrying capacity, the located on rubber plantation area of inhabitants of Rukti Sedyo Village, District of North Raman, East Lampung. The variable observed in this research is the pasture production, carrying capacity, and botany composition. The method used in this research is the method of sueve. This research used 2 treatments with 10 replications on production rubber plants and 25 replications preproduction rubber plants and then the T test was done on fresh pasture production of preproduction and production rubber plants.  The result of this research showed that the pasture production under the shade of preproduction rubber plants and production rubber plants are very real different, that is 3,2:1.  The botany composition on the rubber trees are 16 species of preproduction rubber plants and 7 species of production rubber plants. The production rubber plants area 13 hektares wide can produce 4.131,81kg of dry matter with 0,83 cattle unit/13ha/year or 0,06 cattle unit/ha/year. Even the preproduction rubber plants area 34 hektares wide can produce 24.918,708 kg of dry matter with 5,01 cattle unit/34ha/year or 0,14 cattle unit/ha/year. Key words:  pasture production, carrying capacity.